Evaluating presence of antibodies against citrullinated proteins in relation to rheumatoid arthritis and periodontitis / Lew Pit Hui - Lew, Pit Hui (2019)
Background and objective(s): Presence of antibodies against citrullinated proteins (antiCitP) are highly specific for Rheumatoid Arthritis (RA). Recent studies have revealed the occurrence of citrullination in periodontitis (PD) which can induce anti-CitP production, allowing for a potential link between PD and development of RA. However, conflicting findings have been reported to associate RA and PD in relation to the expression of antiCitP. This study aimed to compare the presence of serum anti-CitP with clinical periodontal and RA parameters in patients with RA and/or PD. Materials and Methods: A total of 80 participants were recruited, each of 20 from those diagnosed with both RA and PD (RAPD), only RA, only PD, or no RA or PD (control). Full mouth periodontal examination was conducted, and 10 mL of serum sample was collected from each participant for quantification of anti-CitP using enzyme-linked immunosorbent assay (ELISA). ESR levels and RA disease duration were also recorded. Results: Highest mean (±SD) levels of serum anti-CitP were found in RAPD group (228.82±219.09 IU/mL) followed by RA group (204.01±202.41 IU/mL), PD group (102.62±75.46 IU/mL) and lowest in healthy group (68.73±52.49 IU/mL). Anti-CitP levels were statistically significant higher in RAPD and RA groups compared to that of healthy group (p < 0.05). Multiple regression analysis to control for age and gender confirmed the statistical significance. Anti-CitP levels were not correlated with any of the clinical periodontal parameters between all four groups. For RAPD and RA groups, no statistical significant correlations were observed between serum anti-CitP levels with ESR and RA disease duration. iv Conclusion: There is a trend for an increase in anti-CitP levels from healthy to PD to RA and RAPD groups. The underlying biological mechanisms for the relationship between PD and RA needs to be further investigated in future studies